PEMANTAPAN MEDIA AUDIO VISUAL TERHADAP MINAT BELAJAR IPA DI SEKOLAH DASAR - Agustina Reni Kosho; Asrul Asrul; Muhammad Faizin (CV. ADIBA AISHA AMIRA, 2025)
Interest in learning is a feeling of liking or interest in something or an activity without anyone telling you to. Power Point media was chosen because in learning it is considered to be able to provide learning in a different way, watching, listening, showing examples in the form of pictures with a larger display, involving students' thinking skills and absorption capacity in finding the knowledge being studied. The aim of this research is: to determine the effect of learning using PowerPoint on interest in learning science in class V of YPPK Santa Maria Kukding Elementary School. The type of research carried out in this research is quantitative research. The design used in this research is Ex Post Facto Design with a quantitative approach. The independent variable in this research is Power Point media (X), the related variable in this research is students' learning interest in science content (Y). This research was carried out at YPPK Santa Maria Kukding Elementary School, Bintang Mountains Regency, Papua Mountains Province. The population in this study was all 30 grade V students of YPPK Santa Maria Kukding Elementary School, Bintang Mountains Regency for the 2023/2024 academic year. Hypothesis testing in this study used the t test (one simple T-test). Based on the results of data analysis, namely the value tcount> ttable (5.242> 1,734), with a significance level of 0.05, namely (0.000 < 0.05), the hypothesis is accepted, meaning it can be concluded that there is an influence of the use of power point media on students' interest in learning. V SD YPPK Santa Maria Kukding, Bintang Mountains Regency”.